Ecological methods in forest pest management - Wainhouse, David (Oxford : Oxford University Press, 2005)
Throughout the world there is a need to control forest insect pests. This text focuses predominantly on insect pests, but many examples relate to fungal pathogens, saome of which are vectored by forest insects. It looks at the development of Integrated Pest Management (IPM).
Description based on print version record.
Includes bibliographical references and index.
Keywords: Pests -- Biological control; Forest management